Pola Komunikasi Interpersonal Generasi Z dalam Membangun Hubungan Pertemanan Digital di Kuningan Jakarta Selatan - Ii Maulana; Siti Qonaah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The transformation of interpersonal communication through the development of new media has changed the way Generation Z builds social relationship, especially digital friendships mediated by Instagram. This study aims to analyze the interpersonal communication patterns of Generation Z in Kuningan, Jakarta Selatan, in building digital friendships through structured interviews with five informants selected by purposive sampling, supported by digital behavior observation, documentation, and source and technique triangulation. The findings reveal that Generation Z communication patterns on Instagram are incremental and contextual: intiated through public feature-based interactions such as story replies and comments, then developing into more intimate dyadic communication through direct message by utilizing multiformat modalities. Text, emoji, and voice notes serve as compensatory strategies for the absence of nonverbal cues. Trust is formed gradually through the accumulation of consistent communication behavior, while self-disclosure is facilitated by the mechanism of online disinhibition. The main obastacels include semantic ambiguity in text message, ghosting phenomena, and limitations in digital identity verification. This study concludes that the effectiviness of Generation Z digital friendships substantially depends on interpersonal empathy, honesty, and relational consistency.